ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI KEPERCAYAAN PELANGGAN TERHADAP KEPUTUSAN PELANGGAN DALAM PENITIPAN JASA INAP HEWAN PELIHARAAN DI JUNIOR PETSHOP KOTA LUBUKLINGGAU - Supriyanto Supriyanto; Yuli Eprianti; Winda Astuti (STMIK Pringsewu, 2021)
The purpose of this study is to determine what factors influence customer confidence in customer decisions in pet inpatient care services at Junior Petshop, Lubuklinggau City. Data collection was carried out by observation and interviews. Data analysis using descriptive. The results of the study are what factors influence customer confidence in customer decisions in pet inpatient care services at Junior Petshop, Lubuklinggau City. Judging from trust, it is influenced by factors such as reputation and perceived quality. Reputation can be important to build a consumer's trust in the seller because the consumer does not have personal experience with the seller. Reputation by word of mouth can also be the key to consumer interest. The appearance and design of the company can also influence the first impression that is formed. Meanwhile, the factors that influence customer decisions are caused by cultural factors, social factors and personal factors. Cultural factors include nationality, religion, racial group and geographic area. Social factors are influenced by the reference group, family, and the role and social status of the community, while personal factors include age and life cycle stage, occupation, economic conditions, lifestyle, and the buyer's personality and self-concept.